NANOG is required to form the epiblast and maintain pluripotency in the bovine embryo - Ortega, M. Sofia (Mol Reprod Dev, 2019)
During preimplantation development, the embryo undergoes two consecutive lineages specifications. The first cell fate decision determines which cells give rise to the trophectoderm and the inner cell mass. Subsequently, the inner cell mass differentiates into hypoblast and epiblast, the latter giving rise to the embryo proper. The transcription factors that govern these cell fate decisions have been extensively studied in the mouse, but are still poorly understood in other mammalian species. In the present study, the role of NANOG in the formation of the epiblast and maintenance of pluripotency in the bovine embryo was investigated. Using a CRISPR-Cas9 approach, guide-RNAs were designed to target exon 2, resulting in a functional deletion of bovine NANOG at the zygote stage. Disruption of NANOG resulted in the embryos that form a blastocoel and an inner cell mass composed of hypoblast cells. Furthermore, NANOG-null embryos showed lower expression of epiblast cell markers SOX2 and HA2AFZ, and hypoblast marker GATA6; without affecting the expression of trophectoderm markers CDX2 and KRT8. Results indicate that NANOG, has no apparent role in segregation or maintenance of the trophectoderm, but it is required to derive and maintain the pluripotent epiblast and during the second lineage commitment in the bovine embryo.